THEOREMS ON GENOCCHI POLYNOMIALS OF HIGHER ORDER ARISING FROM GENOCCHI BASIS - Araci, Serkan; Şen, Erdoğan; Acikgoz, Mehmet (Taiwanese journal of mathematics, 2014)
Recently, Kimet al.[8] constructed a new method to obtain interesting identities related to Euler polynomials of higher order arising from Euler basis. In the present paper, we study to Genocchi polynomials of higher order arising from Genocchi basis by using the method of Kimet al.We also derive many interesting properties related to Genocchi polynomials of higher order. 2010Mathematics Subject Classification: 11S80, 11B68. Key words and phrases: Genocchi polynomials, Genocchi polynomials of higher order, Bernoulli polynomials, Bernoulli polynomials of higher order, Hermite polynomials, Euler polynomials, Euler polynomials of higher order.